1993
DOI: 10.1007/bf02245708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of housing, restraint and chronic treatments withmCPP and sertraline on behavioural responses tomCPP

Abstract: The effects of pretreatments on behavioural responses to activation of 5-HT1C receptors by m-chlorophenylpiperazine (mCPP) were investigated. The hypo locomotor and anxiogenic effects of mCPP (social interaction test) were influenced neither by previous housing (single versus grouped) nor by restraint (2 h, 24 h previously). In the absence of mCPP, 24 h group housing led to decreased social interaction and the restraint procedure led to significant decreases of feeding and locomotion. The hypophagic effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…This is most marked with d-fenfluramine, though also evident with mCPP. This apparent partial tolerance has been observed previously for both compounds (Sills et al 1985;Freo et al 1992;Kennedy 1993;Vickers et al 2000).…”
Section: Discussionsupporting
confidence: 57%
“…This is most marked with d-fenfluramine, though also evident with mCPP. This apparent partial tolerance has been observed previously for both compounds (Sills et al 1985;Freo et al 1992;Kennedy 1993;Vickers et al 2000).…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, increases in anxiety despite overall locomotor suppression are also documented (e.g. social interaction test: Kennedy et al 1993;elevated plus-maze: Fone et al 1996; canopy stretched attend posture test: Grewal et al 1997). Correspondingly, Meert et al (1997) have found that mCPP treated animals appear to be generally aroused, as evidenced by a doserelated increase in plasma prolactin and ACTH levels, in spite of a decrement in locomotor performance.…”
Section: Effects Of Yohimbine On Ueepm Behaviourmentioning
confidence: 90%
“…Moreover, chronic treatments with citalopram and sertaline, two potent SSRIs, were found to attenuate the hypolocomotor effect of mCPP (Maj & Moryl, 1992;Kennedy et al, 1993). Since it is thought that mCPP reduces locomotor activity in rodents by stimulating the 5-HT2C/2B receptors (Kennett & Curzon, 1988;Kennett et al, 1994b), it has been argued that a down-regulation of 5-HT2c,2B recpetors might be responsible for the behavioural tolerance to mCPP occurring after chronic administration of SSRIs (Kennedy et al, 1993;Kennett et al, 1994a). This is reconcilable with the evidence that mCPP inhibits the activity of dopaminergic neurones in the VTA by acting through the 5-HT2C/2B receptors (Prisco et al, 1994).…”
Section: Discussionmentioning
confidence: 99%